2021
DOI: 10.3389/fneur.2021.744749
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Dependent Dynamics of Functional Connectivity Networks During Seizure Termination in Childhood Absence Epilepsy: A Magnetoencephalography Study

Abstract: Objective: Our aim was to investigate the dynamics of functional connectivity (FC) networks during seizure termination in patients with childhood absence epilepsy (CAE) using magnetoencephalography (MEG) and graph theory (GT) analysis.Methods: MEG data were recorded from 22 drug-naïve patients diagnosed with CAE. FC analysis was performed to evaluate the FC networks in seven frequency bands of the MEG data. GT analysis was used to assess the topological properties of FC networks in different frequency bands.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
(103 reference statements)
1
3
0
Order By: Relevance
“…Comparing (D,E) of DTGCN in Figure 6 , it can be found that the difference between the adjacency matrix of generalized seizure and no seizure is greater than that of focal seizure and no seizure, which indicates that generalized seizure can disrupt normal brain connections to a greater extent than focal epilepsy. This is consistent with the previous description in the literature: brain functional connectivity is significantly altered in global seizures [ 31 ]. Comparing (I,J) of DCRNN in Figure 6 , we find that there is no obvious difference in their graph structures.…”
Section: Results Analysissupporting
confidence: 93%
“…Comparing (D,E) of DTGCN in Figure 6 , it can be found that the difference between the adjacency matrix of generalized seizure and no seizure is greater than that of focal seizure and no seizure, which indicates that generalized seizure can disrupt normal brain connections to a greater extent than focal epilepsy. This is consistent with the previous description in the literature: brain functional connectivity is significantly altered in global seizures [ 31 ]. Comparing (I,J) of DCRNN in Figure 6 , we find that there is no obvious difference in their graph structures.…”
Section: Results Analysissupporting
confidence: 93%
“…An iEEG study on patients with different types of epilepsies has shown that the initial part of the rapid discharge at the beginning of a seizure corresponds to a synchrony decrease across brain areas; later parts of the seizure, as well as pre-ictal states, correspond to increased synchrony 10 . Since FC quanti es the synchronicity among regions 45 , we expect the FC between the different iEEG contacts to be lower before the seizure onset and increased later during the seizure course. Our ndings support this notion since FC was higher in ictal compared to interictal and pre-ictal states while the most prominent changes were observed in higher frequency bands (i.e., beta, low-and high-gamma).…”
Section: Discussionmentioning
confidence: 99%
“…MEG studies of patients with childhood absence epilepsy have shown early ictal activity to be predominantly localized to the frontal and parietal cortices. 23,25,26,29 Some groups have also demonstrated altered activity of the precuneus and other regions of the DMN during absence seizures, although the exact nature of these changes was inconsistent between studies. 26,31 Similar to fMRI and EEG, MEG has been used to contrast ictal and subclinical interictal generalized spike-wave discharges in an attempt to uncover the mechanism behind altered consciousness in absence seizures.…”
Section: Evidence From Megmentioning
confidence: 99%